2019
DOI: 10.1002/tafs.10197
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Effects of Avian Predation on Upper Columbia River Steelhead

Abstract: To investigate the cumulative effects of colonial waterbird predation on fish mortality and to determine what proportion of all sources of fish mortality (1 − survival) was due to bird predation, we conducted a mark–recapture–recovery study with upper Columbia River steelhead Oncorhynchus mykiss that were PIT‐tagged and released (N = 78,409) at Rock Island Dam on the Columbia River, USA. We used a state–space Bayesian model that incorporated live detections and dead recoveries of tagged fish to jointly estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(76 citation statements)
references
References 32 publications
3
73
0
Order By: Relevance
“…Large numbers of bald eagles Haliaeetus leucocephalus overwinter in eastern Oklahoma, including the Spavinaw Creek catchment where they target prey, including fishes (Lish 1973). Predation from birds is common for salmonids (Evans et al 2019), and that may have contributed to increased mortality following stocking while hatchery fish were still naive to predators. Difficulties transitioning from hatchery to natural food and behavior may also reduce survival immediately after stocking.…”
Section: Discussionmentioning
confidence: 99%
“…Large numbers of bald eagles Haliaeetus leucocephalus overwinter in eastern Oklahoma, including the Spavinaw Creek catchment where they target prey, including fishes (Lish 1973). Predation from birds is common for salmonids (Evans et al 2019), and that may have contributed to increased mortality following stocking while hatchery fish were still naive to predators. Difficulties transitioning from hatchery to natural food and behavior may also reduce survival immediately after stocking.…”
Section: Discussionmentioning
confidence: 99%
“…We also collated detections of these tags at two sites downstream of Bonneville Dam where biologists sample with portable antennas: within the Columbia River estuary (Towed PIT array–TWX, rkm 75) and at a colony of piscivorous double‐crested cormorants Phalacrocorax auritus and Caspian terns Hydroprogne caspia on East Sand Island (ESANIS, rkm 8), near the mouth of the Columbia River. The ESANIS site is intended to recover PIT tags from depredated fish from cormorants and terns that forage in the Columbia River and estuary downstream from Bonneville Dam (e.g., Evans et al 2019). From these detection data, we were able to generate encounter histories for individual PIT tags that spanned implantation or release within the hatchery, transfer out of the hatchery to the river release location, and nearly the entire freshwater migration corridor from river release site to the Pacific Ocean.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has identified predation by Caspian terns ( Hydroprogne caspia , hereafter “terns”) and double-crested cormorants ( Nannopterum auritum , hereafter “cormorants”) and consumption by California gulls ( Larus californicus ) and ring-billed gulls ( L . delawarensis , collectively hereafter “gulls”) as a substantial mortality factor for some salmonid species and populations in the CRB in some years [ 4 7 ]. Previous studies were largely focused on quantifying the effects of individual breeding colonies [ 4 6 , 8 , 9 ]; however, most salmonid populations, like those originating from the Snake River, must migrate through the foraging ranges of breeding birds from multiple colonies during seaward migration [ 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%